A World with Robots International Conference on Robot Ethics: ICRE 2015 - Aldinhas Ferreira, Maria Isabel; Silva Sequeira, Joao.; Tokhi, Mohammad Osman; E. Kadar, Endre; Virk, Gurvinder Singh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book contains the Proceedings of the International Conference on Robot Ethics, held in Lisbon on October 23 and 24, 2015. The conference provided a multidisciplinary forum for discussing central and evolving issues concerning safety and ethics that have arisen in various contexts where robotic technologies are being applied. The papers are intended to promote the formulation of more precise safety standards and ethical frameworks for the rapidly changing field of robotic applications. The conference was held at Pavilhão do Conhecimento/Ciência Viva in Lisbon and brought together leading researchers and industry representatives, promoting a dialogue that combines different perspectives and experiences to arrive at viable solutions for ethical problems in the context of robotics. The conference topics included but were not limited to emerging ethical, safety, legal and societal problems in the following domains: • Service/Social Robots: Robots performing tasks in human environments and involving close human-robot interactions in everyday households; robots for education and entertainment; and robots employed in elderly and other care applications • Mobile Robots: Self-driving vehicles, autonomous aircraft, trains, cars and drones • Robots used in medicine and for therapeutic purposes • Robots used in surveillance and military functions.
Part I -- 1 Networks of Social and Moral Norms in Human and Robot Agents -- 2 Perceived Autonomy of Robots: Effects of Appearance and Context -- 3 Formalizing Complex Normative Decisions with Predicate Logic and Graph Databases -- 4 A 21st-Century Ethical Hierarchy for Robots and Persons: EH -- 5 Robots & Free Software -- 6 An Intervening Ethical Governor for a Robot Mediator in -- 7 Exploring the Ethical Landscape of Robot-Assisted Search and Rescue -- 8 Reporting Robot Ethics for Children-Robot Studies in Contemporary Peer Reviewed Papers -- 9 A Typology of Liability Rules for Robot Harms -- 10 Safety and Ethical Concerns in Mixed Human-Robot Control of Vehicles -- 11 Leader-Follower Strategies for Robot-Human Collaboration -- 12 Industrial robot ethics: the challenges of closer human collaboration in future manufacturing systems -- 13 Clarifying the Language of Lethal Autonomy in Military Robots -- 14 Safety Issues of the Portuguese Military Remotely Piloted Aircraft Systems -- 15 Robots and the Military: A Strategic View -- 16 The Domestic Robot: Ethical and Technical Concerns -- 17 Robots in Ageing Societies -- Part II Associated Events -- 18 N´os e os Robots / Os Robots e N´os: Insights from an Exhibition -- 19 The Robot steps in: From normative to prospective ethics -- Index.
Keywords: Control engineering; Robotics; Automation; Ethics; Engineering design; Educational technology; Law -- Europe; Bioethics; Control, Robotics, Automation; Moral Philosophy and Applied Ethics; Engineering Design; Digital Education and Educational Technology; European Law; Bioethics